2021
DOI: 10.1038/s41598-021-99845-1
|View full text |Cite
|
Sign up to set email alerts
|

Indoxyl sulfate, a gut microbiome-derived uremic toxin, is associated with psychic anxiety and its functional magnetic resonance imaging-based neurologic signature

Abstract: It is unknown whether indoles, metabolites of tryptophan that are derived entirely from bacterial metabolism in the gut, are associated with symptoms of depression and anxiety. Serum samples (baseline, 12 weeks) were drawn from participants (n = 196) randomized to treatment with cognitive behavioral therapy (CBT), escitalopram, or duloxetine for major depressive disorder. Baseline indoxyl sulfate abundance was positively correlated with severity of psychic anxiety and total anxiety and with resting state funct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 84 publications
3
35
0
Order By: Relevance
“…In our study, we observed elevated levels of the sulfated form of the toxic LCA and GLCA in more severely anxious patients. We have also previously reported increased production of other bacterially-derived sulfates like pcresol sulfate and indoxyl sulfates (Brydges, Fiehn et al 2021) in the PReDICT study participants. Together, these findings suggest that alterations in sulfotransferase activities may occur in the liver of some patients.…”
Section: Gut Metabolites In Depression and Anxietysupporting
confidence: 56%
“…In our study, we observed elevated levels of the sulfated form of the toxic LCA and GLCA in more severely anxious patients. We have also previously reported increased production of other bacterially-derived sulfates like pcresol sulfate and indoxyl sulfates (Brydges, Fiehn et al 2021) in the PReDICT study participants. Together, these findings suggest that alterations in sulfotransferase activities may occur in the liver of some patients.…”
Section: Gut Metabolites In Depression and Anxietysupporting
confidence: 56%
“…The 229 identified metabolites were then repositioned into metabolic pathways [ 28 ]. A total of 52 enriched metabolic pathways were identified, and the most enriched ones are shown in Figure 2 b.…”
Section: Resultsmentioning
confidence: 99%
“…Title and abstract Title and abstract Of the studies evaluated in our review, 21 evaluated therapeutic approaches [10,13,14,[18][19][20][21]26,29,33,[36][37][38]40,43,[48][49][50]55,56,58]. One study assessed arms with bupropion, venlafaxine, and mirtazapine [36].…”
Section: Strobe Itemsmentioning
confidence: 99%
“…Of the studies evaluated in our review, 21 evaluated therapeutic approaches [ 10 , 13 , 14 , 18 - 21 , 26 , 29 , 33 , 36 - 38 , 40 , 43 , 48 - 50 , 55 , 56 , 58 ]. One study assessed arms with bupropion, venlafaxine, and mirtazapine [ 36 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation